Answer:
see explanation
Explanation:
Divide through by 2
2a² - 5a + 3 = 0
To factor the quadratic
Consider the factors of the product of the coefficient of the a² term and the constant term which sum to give the coefficient of the x- term
product = 2 × 3 = 6 and sum = - 5
The factors are - 2 and - 3
Use the factors to split the a- term
2a² - 2a - 3a + 3 = 0 ( factor the first/second and third/fourth terms )
2a(a - 1) - 3(a - 1) = 0 ← factor out (a - 1)
(a - 1)(2a - 3) = 0
Equate each factor to zero and solve for a
a - 1 = 0 ⇒ a = 1
2a - 3 = 0 ⇒ 2a = 3 ⇒ a =
![(3)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/85tww783zdtzzps1k74cyql3cl3s1y42ha.png)